Low Bacterial Co-infection Invalidates the Early Use of Non-anti-Mycoplasma pneumoniae Antibiotics in Pediatric Refractory Mycoplasma pneumoniae Pneumonia Patients - Liu, Jin-Rong; Lu, Jie; Dong, Fang; Li, Hui-Min; Liu, Hui; Tang, Xiao-Lei; Guo, Yong-Li; Zhao, Shun-Ying (Frontiers in Pediatrics, 2018)
Background: Childhood refractory mycoplasma pneumoniae (MP) pneumonia (RMPP) is a lung disease with elevated level of C-reactive protein and severe clinical and radiological deterioration. Whether bacterial co-infection contributes to disease of RMPP and whether inclusion of non-anti-MP antibiotics in treatment regimen would benefit RMPP patients remains elusive. Methods: We retrospectively reviewed the medical records of 675 RMPP children. Traditional bacterial culture and next generation sequencing (NGS) were used to detect bacteria in bronchoalveolar lavage fluid in all the 675 patients and 18 patients respectively. Antibiotics used and clinical outcomes were analyzed along with other clinical measurements. Results: Positive bacterial cultures were only found in 18 out of 675 cases (2.67%) and NGS analyses of another 18 cases did not revealed positive bacterial infection, which were consistent with the results of bacterial cultures. Non-anti-MP antibiotics were utilized in 630 cases (93.33%), even last-line antibiotics, such as glycopeptides or carbapenems, were frequently used. Conclusion: Bacterial co-infection in RMPP was rare and non-anti-MP antibiotics didn’t show any efficacy for early treatment of RMPP patients, which may provide a rationale for restricting the use of non-anti-MP antibiotics in RMPP patients and preventing antibiotic resistance globally.